Effect of long-term betaine supplementation on chemical and physical characteristics of three muscles from the Alentejano pig - Martins, José M (2012)
BACKGROUND: The use of betaine as a dietary supplement to reduce fat deposition and increase lean muscle mass in pigs is increasing. However, there is no available information on its effect on the physical and chemical (i.e. fatty acid (FA) profile) characteristics of pork. RESULTS: The effects of long-term betaine intake (1 g betaine kg−1 diet for 20 weeks) on the chemical and physical characteristics of Musculus Longissimus dorsi, M. biceps femoris and M. semimembranosus from the Alentejano pig were investigated. The contents of total protein, intramuscular lipids (neutral and polar), myoglobin and total collagen as well as the water-holding capacity, physical colour characteristics and FA profile of the three muscles were determined. With the exception of a significant increase in the intramuscular lipid content of M. longissimus dorsi and M. biceps femoris, betaine supplementation did not influence muscle chemical and colour characteristics or body fat deposition. CONCLUSION: These data suggest that long-term betaine supplementation selectively increases intramuscular lipid deposition (a trait related to meat quality) while not affecting other chemical (including the atheroprotective FA profile) and physical characteristics of the Alentejano pig muscles studied.